The origin of cosmic rays - Ginzburg, V. L. (Vitalii Lazarevich), 1916-2009; Syrovatskii, S. I. (Sergei Ivanovich), 1925-1979 (Pergamon Press; [distributed in the Western Hemisphere by Macmillan, New York], 1964)
The Origin of Cosmic Rays examines the astrophysical phenomena that cause cosmic rays. The title details the concerns in the study of tracing the sources of cosmic rays. The text presents the primary cosmic rays on earth, and then proceeds to tackling ling the cosmic magnetic bremsstrahlung radio emission and cosmic rays in the universe. Next, the selection deals with the motion of cosmic rays in the interstellar medium and the origin of cosmic rays. The text also talks about the quantitative galactic theory of the origin of cosmic rays. The book will be of great use to astronomers, astrophys.